양극산화 모드 전환을 통한 기능성 알루미늄 표면 연구 - 박영주(Youngju Park); 정찬영(Chanyoung Jeong) (Biuletyn Uniejowski, 2022)
This research develops an easy-to-use, environmentally friendly method for fabricating functional 1050 aluminum alloy surfaces with excellent corrosion resistance. Functional aluminum surfaces with various nanostructures are fabricated by controlling the experimental conditions of anodizing process. The experiment used a multi-step anodizing process that alternates between two different anodizing modes, mild anodizing (MA) and hard anodizing (HA), together with a pore-widening (PW) process. Among them, the nanostructured surface with a small solid fraction shows superhydrophobicity with a contact angle of more than 170° after water-repellent coating. In addition, the surface with superhydrophobicity is difficult for corrosive substances to penetrate, so the corrosion resistance is greatly improved.